Introductions of two insect species threatened by sea‐level rise in Essex, United Kingdom: Fisher's estuarine moth Gortyna borelii lunata (Lepidoptera: Noctuidae) and Mottled grasshopper Myrmeleotettix maculatus (Orthoptera: Acrididae). Issue 1 (1st December 2016) - Gardiner, T.; Ringwood, Z.; Fairweather, G.; Perry, R.; Woodrow, L.
Abstract : The approaches taken to establish on the Essex coast (south‐east England, UK) new wild populations of the nationally rare Fisher's estuarine moth Gortyna borelii lunata and the locally scarce Mottled grasshopper Myrmeleotettix maculatus differed in both scale and method. The aim of this paper is to describe and contrast the differing introductions and discuss their appropriateness for specific locations. Because of its rarity locally and lack of funding for a large‐scale project, live transport of M. maculatus was a simple, cheap and quick method of introducing the grasshopper to a single receptor site in 2009. To date, the site has continued to support a small breeding population of the grasshopper, which is spreading across the dunes away from its release site. The legally protected status, vulnerability and national rarity of G. borelii lunata resulted in a landscape‐scale project involving the creation of new areas of habitat by establishing the larval food plant for the species at suitable sites, commenced on the north‐east Essex coast in 2006. The aim of this project was to create a network of interconnected sites away from the threats of coastal inundation, thereby securing the future of G. borelii lunata in the UK. From 2008 onwards, a captive‐breeding programme was established at Colchester Zoo, UK, to provide live stock for the Fisher's estuarine moth introduction programme. At the time of writing, 27 new areas of habitat have been created for G. borelii lunata and 20 of these areas were shown to support signs of the moth's larval feeding in 2015. The moth was directly established using stock from the captive‐breeding programme at six of the 20 sites. Abstract : The approaches taken to establish on the Essex coast (south‐east England, UK) new wild populations of the nationally rare Fisher's estuarine moth Gortyna borelii lunata and the locally scarce Mottled grasshopper Myrmeleotettix maculatus differed in both scale and method. The aim of this paper is to describe and contrast the differing introductions, and discuss their appropriateness for specific locations. (Photo: Micky Andrews)